Geographical Health District and Distance Traveled Influence on Clinical Status at Admission of Patients with Gestational Trophoblastic Disease - Silva, Valdete Aparecida Ribeiro da [UNESP]; Maestá, Izildinha [UNESP]; Costa, Roberto Antonio de Araújo [UNESP]; Campos, Aline de Ávila [UNESP]; Braga, Antonio; Horowitz, Neil; Elias, Kevin M.; Berkowitz, Ross (Federação das Associações de Ginecologia e Obstetrícia, 2022)
Objective To assess the potential relationship of clinical status upon admission and distance traveled from geographical health district in women with gestational trophoblastic disease (GTD). Methods This is a cross-sectional study including women with GTD from the 17 health districts from the São Paulo state (I-XVII), Brazil, referred to the Botucatu Trophoblastic Disease Center (specialized center, district VI), between 1990 and 2018. At admission, hydatidiform mole was assessed according to the risk score system of Berkowitz et al. Gestational trophoblastic neoplasia was evaluated using the International Federation of Gynecology and Obstetrics / World Health Organization (FIGO/WHO) staging/risk score. Data on demographics, clinical status and distance traveled were collected. Multiple regression analyses were performed. Results This study included 366 women (335 hydatidiform mole, 31 gestational trophoblastic neoplasia). The clinical status at admission and distance traveled significantly differed between the specialized center district and other districts. Patients referred from health districts IX (β = 2.38 [0.87-3.88], p = 0.002) and XVI (β = 0.78 [0.02-1.55], p = 0.045) had higher hydatidiform mole scores than those from the specialized center district. Gestational trophoblastic neoplasia patients from district XVI showed a 3.32 increase in FIGO risk scores compared with those from the specialized center area (β = 3.32, 95% CI = 0.78-5.87, p = 0.010). Distance traveled by patients from districts IX (200km) and XVI (203.5km) was significantly longer than that traveled by patients from the specialized center district (76km). Conclusion Patients from health districts outside the specialized center area had higher risk scores for both hydatidiform mole and gestational trophoblastic neoplasia at admission. Long distances (>80 km) seemed to adversely influence gestational trophoblastic disease clinical status at admission, indicating barriers to accessing specialized centers.
A influencia do distrito de saude e da distancia viajada sobre o estado cl nico na apresentacao de pacientes com doenca trofoblastica gestacional
Keywords: clinical status; distance traveled; geographical health district; gestational trophoblastic disease; referral center